1994
DOI: 10.3168/jds.s0022-0302(94)76943-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Beet Pulp and Animal By-Products on Milk Yield and In Vitro Fermentation by Rumen Microorganisms

Abstract: Forty-six Holstein cows (30 primiparous) were assigned to one of four dietary treatments arranged as a 2 x 2 factorial experiment during wk 4 to 17 of lactation. Main effects were corn versus dried sugar beet pulp and soybean meal versus animal by-product meal (mixture of meat and bone meal, feather meal, and blood meal). Beet pulp replaced half of the corn at 15% of dietary DM. Diet DM (mean of four treatments) contained 18% alfalfa pellets, 17.4% alfalfa hay, 17.2% corn silage, and 47.1% concentrate. Milk yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
1
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 21 publications
6
44
1
1
Order By: Relevance
“…In consequence, neither was the mean daily NEL intake of the cows different between the treatments nor were the yields of milk, milk fat and milk protein affected. These findings are in agreement with previous studies comparing maize with beet pulp in TMR (Mansfield et al, 1994;Clark and Armentano, 1997;Voelker and Allen, 2003b). It is worth mentioning that both the inclusion level of beet pulp silage in the ration (20% of DM) and the level of milk yield were very high in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In consequence, neither was the mean daily NEL intake of the cows different between the treatments nor were the yields of milk, milk fat and milk protein affected. These findings are in agreement with previous studies comparing maize with beet pulp in TMR (Mansfield et al, 1994;Clark and Armentano, 1997;Voelker and Allen, 2003b). It is worth mentioning that both the inclusion level of beet pulp silage in the ration (20% of DM) and the level of milk yield were very high in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies with fresh beet pulp indicated an increase in milk yield and a decrease in milk fat content Parkins et al, 1986). Experiments with rations containing dried beet pulp have reported inconsistent effects on feed intake, milk yield and fat-corrected milk yield (Mansfield et al, 1994;Clark and Armentano, 1997). However, in all experiments the performance of dairy cows was on a low level.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…Contrary to our results, previous studies reported no effects of the substitution of dried beet pulp for corn grain on milk yield (Kajikawa et al 1990;Mansfield et al 1994;Swain & Armentano 1994;Clark & Armentano 1997). These findings were remarkable because diets based on only corn grain and low fiber were expected to produce more milk.…”
Section: Resultscontrasting
confidence: 99%
“…Non-forage fibre sources have higher available energy values than most forages (Firkins, 1997), higher fibre digestibility (Cunningham et al, 1993) and molar proportions of acetate (Mansfield et al, 1994) when replacing cereal grains, and have a lower NFC content than most starchy cereal grains (NRC, 2001). Beet pulp has a similar range of NDF content as forages but its particle size is generally smaller than that of forages (Allen, 2000) and is unique in its high concentration of neutral detergent soluble fibre, especially pectic substances (Voelker & Allen, 2003;Dann et al, 2007;Murray et al, 2008).…”
Section: Introductionmentioning
confidence: 99%